Probing changes in corticospinal excitability following theta burst stimulation of the human primary motor cortex. Issue 1 (January 2016) - Goldsworthy, Mitchell R.; Vallence, Ann-Maree; Hodyl, Nicolette A.; Semmler, John G.; Pitcher, Julia B.; Ridding, Michael C.
Highlights: Plasticity responses to continuous and intermittent theta burst stimulation (cTBS, iTBS) were assessed using MEP input/output curves. Long-term depression-like response to cTBS was greatest when probed using high stimulus intensities. Long-term potentiation-like response to iTBS was greatest when probed using low stimulus intensities. Abstract: Objective: To determine whether the intensity of transcranial magnetic stimulation (TMS) used to probe changes in corticospinal excitability influences the measured plasticity response to theta burst stimulation (TBS) of the human primary motor cortex. Methods: Motor evoked potential (MEP) input/output (I/O) curves were recorded before and following continuous TBS (cTBS) (Experiment 1; n = 18) and intermittent TBS (iTBS) (Experiment 2; n = 18). Results: The magnitude and consistency of MEP depression induced by cTBS was greatest when probed using stimulus intensities at or above 150% of resting motor threshold (RMT). In contrast, facilitation of MEPs following iTBS was strongest and most consistent at 110% of RMT. Conclusions: The plasticity response to both cTBS and iTBS is influenced by the stimulus intensity used to probe the induced changes in corticospinal excitability. Significance: The results highlight the importance of the test stimulus intensity used to assess TBS-induced changes in corticospinal excitability when interpreting neuroplasticity data, and suggest that a number of test intensities may be required to reliably probe the plasticity response.